INSTRUCTIONAL MEDIA USED BY ENGLISH TEACHERS AT SMPN 2 RANTEPAO (BASED ON STUDENTS’ PERCEPTION) - Rambo, Indhy Fanesa; Taula’bi’, Nilma; Sudarsi, Elim Trika (Publikasi dan UKI Press UKI Toraja., 2024)
The purpose of this study is to find out What kinds of Instructional Media Used by English Teachers at SMPN 2 Rantepao and What are the students’ perception towards Instructional Media Used by English Teachers at SMPN 2 Rantepao. For data processing in this study, researchers used qualitative methods, the strategy used was descriptive qualitative. The subjects of the research were the students SMPN 2 Rantepao. The data in this study were obtained through interviews and observation. The data that has been collected was analyzed in three stages, namely data reduction, data display and conclusion drawing. The results of the study show that kinds of instructional media used English teachers at SMPN 2 Rantepao namely picture, English textbook, whiteboard, dictionary, poster, board marker, laptop, power point, LCD, and loud speaker. Students’ perception towards the use of media used by teachers in teaching English, the most student perception that the use of instructional media was extremely helpful and made easier for them in the learning process. While some perception that it was not beneficial.